If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3(-4 + 2) = -1 Combine like terms: -4 + 2 = -2 x + -3(-2) = -1 Multiply -3 * -2 x + 6 = -1 Reorder the terms: 6 + x = -1 Solving 6 + x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = -1 + -6 Combine like terms: 6 + -6 = 0 0 + x = -1 + -6 x = -1 + -6 Combine like terms: -1 + -6 = -7 x = -7 Simplifying x = -7
| 7x/11=7/11 | | 5h-h-4=-20 | | (3x)+2=8 | | 0.307692307692308-2=x | | 3(x-1)2=6+2(y+1)2 | | 21,000=3,400t+600 | | (3/5)x=1 | | -26+3v=-4(v+3) | | X-6/@ | | 8x-10=3x+25-15-50 | | 18-4x=26 | | 3x+3=-2x+2 | | 7(4n+4)=2(7n-3)+15n | | 43x+4=90 | | -8a-2b+3a-8b= | | 2x+x^2=528 | | 3(x-1)-3=9 | | 40=10+2x-5x | | 2/3:x/80 | | 32(2.14)=64(2.14) | | 3(x-1)=6x-6-3x | | 2345/20 | | 4(x*3)=2(x-6) | | -(5x-10)=-20 | | 4x+9-8=5x+4 | | 21-6m=3m-2m | | 2/3(9m-21)=5 | | w-(7/9)=2/9 | | -2*4=-8 | | 13x+1=2(6x-4)+9 | | 2=xy+y | | c/(9)=2 |